PERFORMANCE ANALYSIS OF SENTUL CIRCUIT ROUNDABOUT AND ALTERNATIF ROAD SENTUL BOGOR - M Farid Alfarizi R; Muhammad Isradi; Amar Mufhidin; Widodo Budi Dermawan; Andri Irfan Rifai; Joewono Prasetijo (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734, 2022)
A roundabout is an intersection equipped with circular lanes and has a design specification and is equipped with traffic equipment. The various patterns of movement will intersect each other, causing conflict points at an intersection. This study aims to determine the performance of the Sentul circuit roundabout and the Sentul alternatif road segment. Traffic data was collected for 3 days using the 1997 MKJI method, then made a traffic simulation using the PTV Vissim.The results of the study showed that the highest traffic volume was on Tuesday, November 23, at: the 9725 pcu/hour roundabout and the alternatif sentul total 2 directions 7865 pcu/hour. Sentul circuit roundabout using MKJI 1997 obtained DS values for each link: weaving area 1 (0.81), weaving area 2 (0.81), weaving area 3 (0.86), weaving area 4 (0.77) and alternatif sentul roads: roundabout direction (0.41) , the direction of Bogor (0.45). PTV Vissim the level of service for the sentul circuit roundabout and the alternative sentul: Sentul circuit roundabout: weaving area 1 (e), weaving area 2 (d), weaving area 3 (c), weaving area 4 (f). section alternative sentul: roundabout direction (b) and Bogor direction (b). alternative solution for scenario 1 by restricting heavy vehicles (HV) during rush hour is obtained DS: link 1 (0.69), link 2 (0.64), link 3 (0.72), link 4 (0.62).